Ribosomal protein RPL22/eL22 regulates the cell cycle by acting as an inhibitor of the CDK4-cyclin D complex. Issue 6 (3rd April 2019) - Del Toro, Neylen; Fernandez-Ruiz, Ana; Mignacca, Lian; Kalegari, Paloma; Rowell, Marie-Camille; Igelmann, Sebastian; Saint-Germain, Emmanuelle; Benfdil, Mehdi; Lopes-Paciencia, Stéphane; Brakier-Gingras, Léa; Bourdeau, Véronique; Ferbeyre, Gerardo; et al.
ABSTRACT: Senescence is a tumor suppressor program characterized by a stable growth arrest while maintaining cell viability. Senescence-associated ribogenesis defects (SARD) have been shown to regulate senescence through the ability of the ribosomal protein S14 (RPS14 or uS11) to bind and inhibit the cyclin-dependent kinase 4 (CDK4). Here we report another ribosomal protein that binds and inhibits CDK4 in senescent cells: L22 (RPL22 or eL22). Enforcing the expression of RPL22/eL22 is sufficient to induce an RB and p53-dependent cellular senescent phenotype in human fibroblasts. Mechanistically, RPL22/eL22 can interact with and inhibit CDK4-Cyclin D1 to decrease RB phosphorylation both in vitro and in cells. Briefly, we show that ribosome-free RPL22/eL22 causes a cell cycle arrest which could be relevant during situations of nucleolar stress such as cellular senescence or the response to cancer chemotherapy. Graphical Abstract: